Biomechanical mechanism of reduced aspiration by the Passy-Muir valve in tracheostomized patients following acquired brain injury: Evidences from subglottic pressure - Han, Xiaoxiao; Ye, Qiuping; Meng, Zhanao; Pan, Dongmei; Wei, Xiaomei; Wen, Hongmei; Dou, Zulin (Frontiers in Neuroscience, 2022)
Objective Aspiration is a common complication after tracheostomy in patients with acquired brain injury (ABI), resulting from impaired swallowing function, and which may lead to aspiration pneumonia. The Passy-Muir Tracheostomy and Ventilator Swallowing and Speaking Valve (PMV) has been used to enable voice and reduce aspiration; however, its mechanism is unclear. This study aimed to investigate the mechanisms underlying the beneficial effects of PMV intervention on the prevention of aspiration. Methods A randomized, single-blinded, controlled study was designed in which 20 tracheostomized patients with aspiration following ABI were recruited and randomized into the PMV intervention and non-PMV intervention groups. Before and after the intervention, swallowing biomechanical characteristics were examined using video fluoroscopic swallowing study (VFSS) and high-resolution manometry (HRM). A three-dimensional (3D) upper airway anatomical reconstruction was made based on computed tomography scan data, followed by computational fluid dynamics (CFD) simulation analysis to detect subglottic pressure. Results The results showed that compared with the non-PMV intervention group, the velopharynx maximal pressure (VP-Max) and upper esophageal sphincter relaxation duration (UES-RD) increased significantly (P < 0.05), while the Penetration-Aspiration Scale (PAS) score decreased in the PMV intervention group (P < 0.05). Additionally, the subglottic pressure was successfully detected by CFD simulation analysis, and increased significantly after 2 weeks in the PMV intervention group compared to the non-PMV intervention group (P < 0.001), indicating that the subglottic pressure could be remodeled through PMV intervention. Conclusion Our findings demonstrated that PMV could improve VP-Max, UES-RD, and reduce aspiration in tracheostomized patients, and the putative mechanism may involve the subglottic pressure. Clinical trial registration [http://www.chictr.org.cn], identifier [ChiCTR1800018686].